Die räumliche Differenzierung klimatologischer Betrachtungsweisen. Ein Vorschlag zur Gliederung der Klimatologie und zu ihrer Nomenklatur - Weischet, Wolfgang (ERDKUNDE, 1956)
The theme of this paper concerns the problem of finding a comprehensive classification of climate which does justice to the subject matter. An attempt is made here to see climate and region as one unit and to adjust the classification of both these objects of research to each other. Suggestions for classification put forward so far, such as those of Geiger and Schmidt (major-, minorand micro-climate) or Scaetta (macro-, meso- and microclimate) have not found general acceptance and the terms which they introduced are used ambiguously. Besides linguistic considerations the reasons for this probably lie in the fact that firstly a mere tripartition is incomplete, and that secondly these relative concepts are impracticable because of the inherent difficulty in separating them from each other and since they Jack any link to concrete properties of the subject matter under consideration. Since each climatic investigation is related to a certain space - because the method employed in each particular case depends largely on the order of size of the investigated area, and even more many characteristics of the climate are directly affected by immobile surface features which can be classified according to size as weil as according to geographical contents - the suggestion is made that the ways of approach in climatology be classified according to size of the area under investigation by following the usual principles of regional classifications. Thus the following fourfold division results: regional climate, sub-regional climate, local climate, and micro-climate. The special properties of these four ranks of climate, typical characteristics of the methods of their investigation and their link with the units of the regional hierarchy are shown in a number of examples.